Multiplication and infectivity of sporidia of Tilletia barclayana, the causal organism of kernel smut of rice - and P.P.S. PANNU, S.S. CHAHAL, GURBAJ SINGH (Indian Phytopathology, 2002)
Potato dextrose agar and host extract media supported maximum radial growth of T. barclayana, followed in sequence by Richard’s, Czapeck’s and glucose nitrate media. Production of both filiform and allantoid sporidia was greater on PDA and host extract media, least on Czapeck’s medium, and nil on Richard’s and glucose nitrate media. The sporidia of the pathogen were capable of germination on the host (Oryza sativa) and non-host plants like Cyperus rotundus, Echinochloa crus-galli, Euchlaena mexicana [Zea mexicana], Sorghum vulgare [S. bicolor] and Zea mays. Maximum tertiary sporidia production was on O. sativa closely followed by E. crus-galli whereas under glasshouse conditions, Z. mays, S. bicolor and E. crus-galli supported maximum sporidia production which was slightly more than that on O. sativa. The production of infected grains was much higher with inoculations by allantoid type of sporidia than that of filiform sporidia. There was significant interaction between sporidia type and sporidiaconcentration for producing the disease. However, there was a decrease in production of infected grains between allantoid and filiform sporidia, with an increase in sporidia concentration. The incubation period and production of teliospores were different in different varieties of the host.